Aqueous Behaviour of Chitosan - D. P. Chattopadhyay; Milind S. Inamdar (International Journal of Polymer Science)
Chitosan, a versatile biopolymer, finds numerous applications in textile processing unit operations such as preparation, dyeing, printing, and finishing. However, the accessibility of this biopolymer by the textile material depends on the viscosity of its solution which in turn is a function of its molecular weight. In this work, therefore, the effect of molecular weight, storage life, presence of electrolyte, and particle size of chitosan on its viscosity was investigated. Chitosan of different molecular weights was synthesized by nitrous acid hydrolysis of parent chitosan solution. The synthesized low molecular weight products were analysed by FTIR spectroscopy. Chitosan of nanoconfiguration was prepared by Ionotropic gelation method and characterized by particle size analyzer. The viscosity of different chitosan solutions was determined using Ubbelohde capillary viscometer. As an extension to this study, the chelation property of chitosan was also evaluated.